Imaging Molecular Expression on Vascular Endothelial Cells by In Vivo Immunofluorescence Microscopy - Judith M. Runnels; Parisa Zamiri; Joel A. Spencer; Isreal Veilleux; Xunbin Wei; Alexei Bogdanov; Charles P. Lin (Molecular Imaging)
Molecular expression on the vascular endothelium is critical in regulating the interaction of circulating cells with the blood vessel wall. Leukocytes as well as circulating cancer cells gain entry into tissue by interacting with adhesion molecules on the endothelial cells (EC). Molecular targets on the EC are increasingly being explored for tissue-specific delivery of therapeutic and imaging agents. Here we use in vivo immunofluorescence microscopy to visualize the endothelial molecular expression in the vasculature of live animals. High-resolution images are obtained by optical sectioning through the intact skin using in vivo confocal and multiphoton microscopy after in situ labeling of EC surface markers with fluorescent antibodies. Other vascular beds such as the bone marrow and ocular blood vessels can be imaged with little or no tissue manipulation. Live imaging is particularly useful for following the dynamic expression of inducible molecules such as E-selectin during an inflammatory response.